ENGLISH AS A MEDIUM OF INSTRUCTION IN INDONESIAN PRIMARY AND SECONDARY EDUCATION: Theory and reality - Imam Khasbani (Englisia: Journal of Language, Education, and Humanities, 2019)
The globalization phenomenon marked by the flow of people movements, the advancement of informational technology, and the shrinking price of transportation has brought people around the world into one global community. Comprised by people from diverse linguistic backgrounds, this community sees the need to use a common language to bridge the communication gap. With a long-established economic and political power, English comes to the forefront as a global lingua franca. With its growing and pervasive influence, the need to learn English has never become more apparent. This need is often translated by government into language-in-education policy. This paper, to start with, will observe how language policy and globalization build a causal relationship. In the section that follows, language-in-education policy in Indonesian context will be presented. The following part will move on to discuss the use of EMI in Sekolah Berstandar Internasional (SBI)-International Standard School in Indonesia. In the end, a reflection and conclusion of EMI in Indonesia context will be discussed. In doing so, this paper employs literature study approach to explore the EMI practice in Indonesian schools. All relevant information was collected from several sources such as books and journal articles. The information was then utilised to build on discussions on existing theoretical framings, language policy and globalization, and on language-in-education policy and practice in Indonesia.